2018
DOI: 10.3233/bmr-170871
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a semi-electronic tissue compliance meter to assess muscle stiffness

Abstract: The STCM provides valid and reliable measurements of tissue stiffness. Further study is needed to provide norm values for different body regions and to reveal alterations in patients with musculoskeletal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…The measurement principle of Indentometer re-sembles that of a durometer or a tissue compliance meter, and the usefulness of both in the evaluation of skin induration 21,31 and muscle stiffness in the calf has been previously reported. 42 However, Moloney et al reported that quantifying fibrosis with the tissue compliance meter was difficult and that there is no preferred methodology for the evaluation of neck skin fibrosis. 43 The usefulness of a durometer or tissue compliance meter in the evaluation of skin induration is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement principle of Indentometer re-sembles that of a durometer or a tissue compliance meter, and the usefulness of both in the evaluation of skin induration 21,31 and muscle stiffness in the calf has been previously reported. 42 However, Moloney et al reported that quantifying fibrosis with the tissue compliance meter was difficult and that there is no preferred methodology for the evaluation of neck skin fibrosis. 43 The usefulness of a durometer or tissue compliance meter in the evaluation of skin induration is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of tissue stiffness assessment via ultrasound elastography as well as via myometry and indentometry has been recently documented (Pruyn et al, ; Salavati et al, ; Wilke et al, ). Because mechanoadaptation of collagenous tissues does not always go along with the adaptation of related skeletal muscles (Mersmann et al, ), it is suggested to enhance the incorporation of fascial tissue assessments in future therapeutic as well as scientific investigations in the field of sports medicine (Zuegel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We measured the muscle's resistance against deformation as a surrogate measure for muscle stiffness (Simons and Mense, 1998 ; Wilke et al, 2018 ) using a custom-built indentometer device. The handheld device was used in a previous study to non-invasively investigate back muscle stiffness (Kett and Sichting, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The handheld device was used in a previous study to noninvasively investigate back muscle stiffness (Kett and Sichting, 2020). A prior study by Wilke et al (2018) on the gastrocnemius muscle indicates an excellent test-retest reliability (intraclass correlation coefficient: 0.84) for the indentometer device (Wilke et al, 2018). As described by Kett and Sichting (2020), the device contains a load cell (Compression Load Cell FX1901, TE Connectivity, Schaffhausen, Switzerland) and a membrane potentiometer (ThinPot 10 kOhm, Spectra Symbol, Salt Lake City, USA) to measure the resistance force and displacement of a circular indentation probe (Ø 11.3 mm) (Kett and Sichting, 2020).…”
Section: Stiffness Measurementmentioning
confidence: 99%